Role-play and Speaking Anxiety: A Case Study in an Online English Speaking Class - Selvie Gaman Goram; Adaninggar Septi Subekti (DBSMB, Vocational College of Universitas Gadjah Mada, 2022)
Though studies about role-plays may be frequent, studies specifically investigating the possible relation between role-plays and speaking anxiety may still be very rare, particularly in the Indonesian second/foreign (L2) context, despite anxiety being a quite widespread phenomenon among language learners. Hence, the present study was conducted to investigate Indonesian learners' extent of participation in role-play activities in an online English speaking class and learners’ and teachers' views about role-plays concerning speaking anxiety. The study employed a qualitative case study using online observations and interviews. The participants were 25 English education department learners and two teachers implementing role-plays. Through observations, the study found that role-plays were unable to make most of the learner participants voluntarily participate in class. Through interviews analysed using Thematic Analysis, the study found three themes. Learners' nervousness and fear of making mistakes negatively affected their role-play performances. Authentic situations in role-plays allowed them to feel more comfortable. Next, preparing role-play for performances in groups lessened learners’ anxiety. It is suggested that teachers offered learners choices whether to do live role-plays or show pre-recorded one. The latter may reduce anxiety and make it possible for learners to redo some parts, allowing them to showcase their best possible performance.